Chemical Topping and Planting Density Interactively Affect Cotton Growth and Partitioning Index - Yutong Zhang; Yongfan Chen; Shuai Sun; Pengzhong Zhang; Zeshan Zhang; Xuejiao Wang; Xuelian Tang; Mingfeng Yang; Dao Xiang; Sen Wang; Fen Ji; Lizhen Zhang (Agronomy)
Due to the labor shortage, replacing manual topping with chemical topping has become an important practice in cotton-producing areas such as Xinjiang, China. Similarly, increasing planting density is a common strategy to enhance cotton yields. This study aimed to quantify the interactive effects of chemical topping and planting density on cotton growth and assimilate partitioning. To achieve this, a two-year (2020–2021) field experiment was conducted in Xinjiang, China. The main plots were assigned low (15 plants m−2) or high plant density (25 plants m−2), and the subplots were chemical topping using heavy amounts of mepiquat chloride (MC) or manual topping. The dynamics of dry matter accumulation and partitioning in cotton were well quantified using a beta-growth function with an overall nRMSE of 11.5%. Results indicated that chemical topping increased aboveground dry matter maximum by 4.88%, fruit dry matter maximum by 17.9% and seed cotton yield by 14.0% compared to manual topping. At low plant density, the partitioning index between vegetative and reproductive organs showed no significant differences. However, at high plant density, the time when 50% of assimilate partitioning to reproductive organs for chemical topping was 2.6 physiological days (under optimal temperature conditions) delayed than that for manual topping, resulting in a 2.7 physiological days delay in the time that fruits reached maximum growth rate. The results of the study suggest that applying chemicals for topping a little earlier in high-density planting could reduce the negative effects of delayed boll growth and promote carbon assimilate partitioning to fruit growth.